Is there a difference between the effects of phytoestrogens and non-phytoestrogens medicinal plants on sexual health? A systematic review and meta-analysis - Masoumeh Sayahi; Afsaneh Keramat; Firoozeh Nourimand1 Ph.D. Candidate; Hakimeh Mohammadzadeh (Shahid Sadoughi University of Medical Sciences, 2023)
Abstract Background: The quality of life of a person and her sexual partner is impacted by sexual function. Sexual function disorders have a significant prevalence in society. There are different treatments for sexual disorders, including herbal therapies. Objective: This study aimed to do a comparison of phytoestrogens and non-phytoestrogens medicinal plant's effects on sexual health in pre- and postmenopausal women. Materials and Methods: This systematic review and meta-analysis was performed to identify relevant articles in electronic databases such as Web of Science, Scopus, PubMed, Cochrane Library, Google Scholar, and SID for English- and Persian-language articles published up to December 2021. The Cochrane collaboration tool was used to assess the risk of bias. Heterogeneity was assessed using I2 statistics. Results: Of 5428 records retrieved by searching the databases, after removing duplicate and irrelevant articles, 39 articles were included based on the inclusion criteria in the study. Finally, 18 articles with 1299 participants were included in the meta-analysis. 18 randomized clinical trial studies of phytoestrogens (n = 13) and non-phytoestrogens (n = 5) plants that used the female sexual function index questionnaire and reported the mean difference (MD) and standard deviation were included in the meta-analysis. The effects of phytoestrogens and non-phytoestrogens plants on the sexual health of postmenopausal women appear to differ significantly from one another, according to the meta-analysis (MD = 7.59; 95% CI = 4.56-10.60 and MD = 3.19; 95% CI = 1.25-5.13, respectively) but this difference was not observed in premenopausal women. Conclusion: The effect of phytoestrogens plants is more in menopausal women, and they can be advised to use these herbs.